2015
DOI: 10.1680/jgein.15.00017
|View full text |Cite
|
Sign up to set email alerts
|

Frictional behaviour of three critical geosynthetic interfaces

Abstract: This paper's scope is the shear interaction mechanisms of three critical geosynthetic interfaces (geotextile/geomembrane; drainage geocomposite/geomembrane and soil/geomembrane) typically used for lined containment facilities such as landfills. A large direct shear machine was used to carry out 159 geosynthetic interface tests. The results showed strain softening behaviour, a very small dilatancy, 0.1-1 mm, and non-linear failure envelopes at normal stress range of 25-500 kPa. The three types of interfaces pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 35 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The conventional direct shear test is a popular test to determine the mechanical behavior of interfaces and estimate fundamental parameters such as friction angle (Vangla and Gali, 2016;Bacas et al, 2015;Rouse et al, 2008;Bergado et al, 2006).…”
Section: Design Of Test Setupmentioning
confidence: 99%
“…The conventional direct shear test is a popular test to determine the mechanical behavior of interfaces and estimate fundamental parameters such as friction angle (Vangla and Gali, 2016;Bacas et al, 2015;Rouse et al, 2008;Bergado et al, 2006).…”
Section: Design Of Test Setupmentioning
confidence: 99%
“…Currently, the research on the interface characteristics of reinforced soil is mainly based on direct shear tests and pull-out tests. B. M. Bacas et al [5] conducted large direct shear tests to investigate the frictional characteristics of three critical interfaces: geogrid-soil, geosynthetic membrane-soil, and geosynthetic membrane-geogrid. The results revealed that frictional behavior is the primary factor influencing the behavior of these interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Landfills are an important structure in our modern society and are designed to allow maximum accumulation of wastes in the least space and prevent environmental contamination [1]. Landfills usually consist of lining system either as a base liner and/or capping system.…”
Section: Introductionmentioning
confidence: 99%